2016
DOI: 10.1055/s-0035-1561330
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pyrylium and Thiopyrylium Photooxidants in Metal-Free Ring-Opening Metathesis Polymerization

Abstract: Materials and Methods. Dichloromethane (CH 2 Cl 2) and acetonitrile (CH 3 CN) were obtained from a solvent purification system. 1 H NMR spectra were recorded on Bruker AVance 300 MHz or 500 MHz spectrometers. Chemical shifts are reported in delta (δ) units, expressed in parts per million (ppm) downfield from tetramethylsilane using the residual protio-solvent as an internal standard (CDCl 3 , 1 H: 7.26 ppm; DMSO-d 6 , 1 H: 2.50 ppm and 13 C: 39.5 ppm). Gel permeation chromatography (GPC) was performed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Further studies found that PC with strongly excited oxidability will lead to descent of monomer conversion rate and/or even polymerization inhibition. In comparison to thiopyrane‐based catalysts and pyrane‐based catalysts, it revealed that 2,4,6‐tris(4‐methoxyphenyl)thiopyran salt was the best PC for polymerization control among these three typical kinds of PCs 86 . Moreover, the conversion rate of monomer was higher in the air (87%) than in the nitrogen atmosphere (80%) 87 .…”
Section: Visible Light Controlled Cationic Living Polymerizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Further studies found that PC with strongly excited oxidability will lead to descent of monomer conversion rate and/or even polymerization inhibition. In comparison to thiopyrane‐based catalysts and pyrane‐based catalysts, it revealed that 2,4,6‐tris(4‐methoxyphenyl)thiopyran salt was the best PC for polymerization control among these three typical kinds of PCs 86 . Moreover, the conversion rate of monomer was higher in the air (87%) than in the nitrogen atmosphere (80%) 87 .…”
Section: Visible Light Controlled Cationic Living Polymerizationmentioning
confidence: 96%
“…In comparison to thiopyrane-based catalysts and pyrane-based catalysts, it revealed that 2,4,6-tris(4-methoxyphenyl)thiopyran salt was the best PC for polymerization control among these three typical kinds of PCs. 86 Moreover, the conversion rate of monomer was higher in the air (87%) than in the nitrogen atmosphere (80%). 87 In recent work, it has been found that the counter ion of the catalyst affects the stereoscopic regularity of the polymer.…”
Section: Development Of Photo-redox Catalysts In Photo-controlled Cat...mentioning
confidence: 97%
“…The reduced PC •− terminates the catalytic loop by reducing the propagating species to provide a polymer chain ( Scheme 12B ). Boydston and co-workers [ 91 ], systematically studied various pyrylium and thiopyrylium PCs ( Scheme 13 ). It is necessary for these PCs having a high excited-state redox potential to oxidize the enol ether initiators.…”
Section: Reviewmentioning
confidence: 99%